A religião e os limites da técnica : aproximações e distanciamentos a partir do pensamento de Jürgen Habermas - Perovano, Mauricio Fernandes (2014)
Religion and technics, even with different impacts and moments in the architectonic of Jürgen Habermas"s thought, end up constituting as referential dialogic themes in the work of this author, from which he structures his thought in a theoric growing that extends from his early essays to his most recent writings. The objective of this dissertation is, from a literature review, to analyze the approaches performed by Habermas about these dialogical poles explaining movements and theoretical frameworks developed in each step. We propose to work at first the concept of technic explaining the influence inherited from Frankfurt School, as well as their reconstructions and proposals to the impacts of an instrumented reason in society. The culmination of Habermas' analysis about the techno-scientific knowledge will be the delineation of normative ethical limits of such a knowledge and at the same time exposing the pathologies and shortcomings of a strategic reason, or merely related-to-end , which culminates with his proposal of a “mitigated naturalism”. From this theoretical horizon will work the concept of religion and its importance in today's theoretical framework of Habermas. Finally, we analyse his approach about the concept of religion and the importance of this movement in the lurch about this interpretative turn about this, culminating with his repositioning inside the thought of such author.